Factors Affecting the Formulation of Carbamazepine Extended Release Tablet - Samer H. Aziz; Alaa A. Abdulrasool; Ahmed A. Hussein (College of Pharmacy University of Baghdad, 2017)
Carbamazepine is an anticonvulsant agent which acts on the central nervous system and used for the treatment of epilepsy. Carbamazepine was formulated as an oral extended release tablets using ethyl cellulose as retardant substance. Different types of tablets additives such as cellulose materials (sodium carboxymethyl cellulose  and microcrystalline cellulose ), lactose, calcium phosphate and solubilizing agents ( sodium lauryl sulphate and polyethylene glycol 6000) were utilized to study their effect on the release profile of drug from ethyl cellulose matrices. It was found that sodium carboxymethyl cellulose increased the carbamazepine release and the same effect was obtained when the same amount of microcrystalline cellulose used. The result also showed that sodium lauryl sulphate greatly enhanced the release of the drug compared to polyethylene glycol 6000. Also incorporating lactose led to an increase in the release of the drug while utilization of calcium phosphate slowed down the release of the drug.  The results of this study revealed that formula  which composed of 4% ethyl cellulose, 5% sodium carboxymethyl cellulose, as well as 25.6% of lactose and 1% magnesium stearate is comply with United State Pharmacopea XXVIII and showed best  release profile comparable to that of the brand product Tegretol CRÂÂÂÂÂ®. The shelf life was 3.6 years for the selected formula. Key word: Carbamazepine, Ethyl cellulose, Extended release.